The relationship between organizational justice with job satisfaction and organizational citizenship behavior - Indahyati, Nurul; Sintaasih, Desak Ketut (International research journal of management, IT and social sciences, 2019)
This study aims to explain the effect of organizational justice on job satisfaction and organizational citizenship behavior. The technique used to test the research hypothesis used Structural Equation Modeling (SEM) analysis techniques using SMARTPLS assistance, using IBM SPSS Statistics 22, and 65 respondents in this study, taken using Purposive Sampling techniques. The results of the study show that (1) distribution justice has a positive and significant effect on job satisfaction. (2) procedural justice has a positive and not significant effect on job satisfaction. (3) interactional justice has a positive and not significant effect on job satisfaction. (4) justice distribution has a positive and insignificant effect on organizational citizenship behavior. (5) procedural justice has a positive and insignificant effect on organizational citizenship behavior. (6) interactional justice has a positive and insignificant effect on organizational citizenship behavior. (7) job satisfaction has a positive and significant effect on organizational citizenship behavior.